Expression of human cytochrome p450 3A4 gene in Schizosaccharomyces pombe - Steven Kelly (Biologia, 2008)
Heterologous expression systems can be utilized to great advantage in the study of cytochrome P450 enzymes.P450 3A4 is one of the major forms of cytochrome P450 found in liver. It is also involved in the metabolism of numerouswidely used drugs and xenobiotics. In the present study human liver cytochrome P450 3A4 gene was transferred intothe fission yeast Schizosaccharomyces pombe via two different S. pombe expression vectors carrying thiamine repressiblepromoter – nmt1 (pREP42) and constitutive promoter – adh1 (pART1). Heterologously expressed cytochrome P450 3A4 wasdetected in the cells grown in minimal (EMM) or rich medium (YEL) containing 0.5% (w/v) glucose. A typical cytochromeP450 peak for 3A4 was observed at 448 nm in microsomal fraction. The presence of heterologous expression of 3A4 formwas also determined by SDS-PAGE and it molecular mass was identified as 52 kDa. The enzyme activity was confirmed byHPLC analysis, using testosterone as substrate.